Respostas
respondido por:
0
Para resolver basta voce substituir todos os ``x`` da funcao pelo valor pedido.
a) f(0)=0ao quadrado - 2.0 +1 = 1
b) f(2)= 2 ao quadrado - 2.2 +1 = 4 - 4 + 1 = 1
c) f(-3)= -3 ao quadrado - 2. -3 + 1 = 9 + 6 + 1= 16
d) f(raiz de 2) = raiz de 2 ao quadrado - 2.raiz de 2 + 1 = raiz de 4 - 2.raiz de 2 +1 =
2 - 2.raiz de 2 + 1 = 2.raiz de 2 + 1
a) f(0)=0ao quadrado - 2.0 +1 = 1
b) f(2)= 2 ao quadrado - 2.2 +1 = 4 - 4 + 1 = 1
c) f(-3)= -3 ao quadrado - 2. -3 + 1 = 9 + 6 + 1= 16
d) f(raiz de 2) = raiz de 2 ao quadrado - 2.raiz de 2 + 1 = raiz de 4 - 2.raiz de 2 +1 =
2 - 2.raiz de 2 + 1 = 2.raiz de 2 + 1
Perguntas similares
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás